Exports, R&D and Productivity: A test of the Bustos-model with enterprise data from France, Italy and Spain - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper uses comparable firm level data from France, Italy and Spain to test a hypothesis derived by Bustos (AER 2011) in a model that explains the decision of heterogeneous firms to export and to engage in R&D. Using a non-parametric test for first order stochastic dominance it is shown that, in line with this hypothesis, the productivity distribution of firms with exports and R&D dominates that of exporters without R&D, which in turn dominates that of firms that neither export nor engage in R&D. These results are in line with findings for Argentina reported by Bustos, and with findings for Germany and Denmark. The model, therefore, seems to be useful to guide empirical work on the relation between exports, R&D and productivity.
Keywords: F14; 330; Exports; R&D; productivity; EFIGE data; France; Italy; Spain